Women Sculptors Awarded at the First São Paulo Biennials and the Building of Artistic Recognition. The Cases of Maria Martins and Mary Vieira - Marina Mazze Cerchiaro (OBOE, 2023)
This article examines the awards given to women sculptors at the first São Paulo Biennials (1951-1965), with a focus on the participation of Maria Martins and Mary Vieira, two award-winning Brazilian sculptors who have very different trajectories and productions. Understanding the biennials as a legitimizing sphere and a social network that brings together people, objects, and institutions, I aim to demonstrate how these events were important in building the artistic recognition of Maria Martins and Mary Vieira.